Improving front crawl with continuous short-delayed video feedback - Scurati, R.; Signorini, G.; Mariucci, L.; Formenti, D.; Invernizzi, P. L. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Coaches use several methods to analyze elite athletes' performances and define the most suitable training practices. Quantitative (competition performance, biomechanics, psychological and physiological parameters) and qualitative (technical execution) assessments serve this purpose. Video-based approaches allow quantitative and qualitative evaluations but are specifically instrumental in examining the swimmer's technique, a crucial component permanently addressed throughout the swimmer's competitive activity. Therefore, coaches frequently use video analysis, even if it implies time-consuming efforts to shoot, digitalize, and process their swimmer's video recordings. However, by doing this, coaches can detect all technical issues, especially from underwater views, and provide adequate corrections to swimmers (Mooney et al., 2016). In physical education, practical mobile devices allow boost instructions simply by video captures or thanks to dedicated apps for video analysis (Laughlin et al., 2019), often free. Apps are generally easy to use with aerial recordings, but unfortunately, they do not entirely respond to the swimming needs that should profit from additional underwater visions. Action sports cameras are fit for underwater motion analysis (Bernardina et al., 2016). Still, they cannot provide real-time streaming due to signal loss when immersed, reducing their practicality for underwater video shooting to satisfy immediate didactic purposes. Nevertheless, with alternative underwater cameras and open-source software such as Kinovea, performers can receive immediate video feedback only with a few seconds delay. The visual information the performers receive can effectively support verbal feedback coaches or teachers commonly provide during training or education (Guadagnoli et al., 2002). Hence, the benefits from video-based provisions are not confined to elite athletes. For example, video supports have been used successfully in swim teaching (Scurati et al., 2019; Syahrastani, 2014) to complete ordinary educational methods such as verbal instructions, teacher demonstrations, and drawings. Furthermore, by video-based solutions to watch previously executed actions, the performers can receive additional feedback enriching individuals' sensory perceptions (SteMarie, 2013). Coaches and teachers are facilitated in guiding swimmers' attention, focusing on the more accurate and efficient technical execution of the stroke. This study with young competitive swimmers aimed to investigate the effects on the front crawl performance and technique of supplementation of different forms of video feedback (immediate, postponed, none) by employing relatively practical video devices during swim training.